2016
DOI: 10.1073/pnas.1604872113
|View full text |Cite
|
Sign up to set email alerts
|

Box C/D guide RNAs recognize a maximum of 10 nt of substrates

Abstract: Box C/D RNAs guide site-specific 2′-O-methylation of RNAs in archaea and eukaryotes. The spacer regions between boxes C to D′ and boxes C′ to D contain the guide sequence that can form a stretch of base pairs with substrate RNAs. The lengths of spacer regions and guide-substrate duplexes are variable among C/D RNAs. In a previously determined structure of C/D ribonucleoprotein (RNP), a 12-nt-long spacer forms 10 bp with the substrate. How spacers and guide-substrate duplexes of other lengths are accommodated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The antisense boxes recognize sequences in target RNAs resulting in the fifth nucleotide upstream of the D or D′ box being 2′-O-methylated by the methylase fibrillarin [1], which is properly positioned in the complex. The antisense boxes in eukaryotes vary in length (10–21 nt), but only a maximum of 10 nt can be used for modifications, due to the structure of the snoRNP [23]. With a few exceptions, such as the targeted U6 snRNA [24], SNORDs modify ribosomal RNAs at around 100 sites.…”
Section: The Classic Picture Of Snornasmentioning
confidence: 99%
“…The antisense boxes recognize sequences in target RNAs resulting in the fifth nucleotide upstream of the D or D′ box being 2′-O-methylated by the methylase fibrillarin [1], which is properly positioned in the complex. The antisense boxes in eukaryotes vary in length (10–21 nt), but only a maximum of 10 nt can be used for modifications, due to the structure of the snoRNP [23]. With a few exceptions, such as the targeted U6 snRNA [24], SNORDs modify ribosomal RNAs at around 100 sites.…”
Section: The Classic Picture Of Snornasmentioning
confidence: 99%
“…Several RNA-free Nop5-fibrillarin structures showed an even greater range of NTD placement through rotation around the hinge N (Ye et al 2009). Interestingly, when Ss box C/D RNP was crystallized using a symmetric box C/D RNA and the corresponding target RNA, NTD and the bound fibrillarin was observed to be placed perfectly for catalyzing methylation of the target nucleo-tide (Lin et al 2011;Yang et al 2016). This conformation of NTD is believed to represent one competent for catalysis.…”
Section: Evidence For Structural Diversity Within the C/d Rnp Family mentioning
confidence: 99%
“…By regulating the box C/D RNA stem or by changing Nop56/58 conformation, each snoRNP may form its function-specific assembly. For instance, though the work of Yang and coworkers elegantly demonstrated that the in vitro assembled Ss mono-box C/D RNP contains a tight and narrow target-binding channel allowing for a constant pairing of 10-nt duplex (Yang et al 2016), the work by van Nues and Watkins showed that the C ′ /D ′ motifs in yeast snR13, snR48, and U18 could guide methylation of two nucleotide positions of the target RNA, suggesting a structural plasticity in snoRNPs especially around the C ′ /D ′ motif (van Nues and Watkins 2017). However, it remains to be shown experimentally how these snoRNPs accommodate the plasticity.…”
Section: Why Do Box C/d Rnps Have Multiple Conformations?mentioning
confidence: 99%
“… 40 Interestingly, recent structural analysis of archaeal sRNPs indicate that only 10 basepaired nucleotides can be accommodated during catalysis, leading to the suggestion that the additional basepairing interactions facilitate accurate and efficient snoRNP recruitment and that the subsequent unwinding, which is necessary for modification, extends the residence time of the snoRNA on the pre-rRNA to prevent premature or mis-folding of the target site. 41 …”
Section: Introductionmentioning
confidence: 99%